The impact of a patient's engagement in their health on the magnitude of limitations and experience following upper limb fractures. (January 2020) - Jayakumar, Prakash; Teunis, Teun; Vranceanu, Ana Maria; Williams, Mark; Lamb, Sarah; Ring, David; Gwilym, Stephen
Abstract : Aims: Patient engagement in adaptive health behaviours and interactions with their healthcare ecosystem can be measured using self-reported instruments, such as the Patient Activation Measure (PAM-13) and the Effective Consumer Scale (ECS-17). Few studies have investigated the influence of patient engagement on limitations (patient-reported outcome measures (PROMs)) and patient-reported experience measures (PREMs). First, we assessed whether patient engagement (PAM-13, ECS-17) within two to four weeks of an upper limb fracture was associated with limitations (the Quick Disabilities of the Arm, Shoulder and Hand questionnaire (QuickDASH), and Patient-Reported Outcome Measurement Information System Upper Extremity Physical Function computer adaptive test (PROMIS UE PF) scores) measured six to nine months after fracture, accounting for demographic, clinical, and psychosocial factors. Secondly, we assessed the association between patient engagement and experience (numerical rating scale for satisfaction with care (NRS-C) and satisfaction with services (NRS-S) six to nine months after fracture. Methods: A total of 744 adults with an isolated fracture of the proximal humerus, elbow, or distal radius completed PROMs. Due to multicollinearity of patient engagement and psychosocial variables, we generated a single variable combining measures of engagement and psychosocial factors using factor analysis. We then performed multivariable analysis with p < 0.10 on bivariate analysis. Results: Patient engagement and psychosocial factors combined to form a single factor (factor 1) accounting for 20% (QuickDASH, semi-partial R 2 = 0.20) and 14% (PROMIS UE PF, semi-partial R 2 = 0.14) of the variation in limitations six to nine months after fracture. Factor 1 also accounted for 17% (NRS-C, semi-partial R 2 = 0.17) of variation in satisfaction with care, and 21% (NRS-S, semi-partial R 2 = 0.21) of variation in satisfaction with services. Demographic factors (age, sex, work status) and measures of greater pathophysiology (type of fracture, high-energy injury, post-surgical complications), accounted for much less variation. Conclusion: Patients who actively manage their health and demonstrate effective emotional and social functioning share a common underlying trait. They have fewer limitations and greater satisfaction with care during recovery from upper limb fractures. Future efforts should focus on evaluating initiatives that optimize patient engagement, such as patient education, coaching, and a communication strategy for healthcare professionals. Cite this article: Bone Joint J 2020;102-B(1):42–47